Investigation of key operational factors impacting phosphorus removal and recovery from wastewater treatment plants - Barreiros, Srđana Kolaković Oliveira (2022)
Nutrient and micropollutant removal, as well as resource recovery, are some of the major current concerns in the wastewater treatment field. Wastewater treatment plants (WWTPs) need solutions to quickly tackle these emerging problems and operate as sustainably as possible. Therefore, this thesis focused on providing insight into some of the major challenges in these fields, such as: i) factors influencing efficient enhanced biological phosphorus removal (EBPR) and its microbial community structure; ii) the biotransformation of an important micropollutant (diclofenac) in the EBPR process and iii) phosphorus and carbon solubilisation from WWTP sludge for resource recovery. EBPR is a complex process where specific bacteria are used for phosphorus removal from the bulk liquid. The most important polyphosphate accumulating organism (PAO) is “Candidatus Accumulibacter phosphatis”, that comprises of phylogenetically different Types, clades and subclades, whose metabolism can be influenced by specific conditions. A reactor enriched with Accumulibacter (> 85 %) was operated for over a one-year period, and identification at the sub-clade level was necessary to correlate the specific identity of the Accumulibacter group with the observed reactor performance. The carbon feeding rate proved to be crucial for the expression of different metabolisms, where a fast-feeding rate resulted in a mixed phosphate/glycogen accumulating metabolism leading to poor P removal (< 30 %) that correlated with clusters ii and iii of Accumulibacter IIc, while a slow carbon feeding rate resulted in complete phosphorus removal and an abundance of cluster i. This work showed that some organisms commonly recognised as PAO do not promote efficient phosphorus removal and there is a need to recharacterize the organisms within the Accumulibacter group. Removal of micropollutants is another emerging concern, especially since some micropollutants such as diclofenac have been shown to be near-recalcitrant in conventional WWTPs. Additionally, some physical/chemical processes have been shown to produce transformation products that are more toxic than the parent compound. Diclofenac biotransformation was investigated in the EBPR process, where the metabolic pathway and toxicity of diclofenac by-products were also assessed. Although Accumulibacter did not appear to transform diclofenac as efficiently as other bacteria (e.g., nitrifiers), it was found to still contribute towards its detoxification. Furthermore, a correlation was observed between the quantity of diclofenac biotransformation and Accumulibacter Type, which could suggest that enrichment of Type II Accumulibacter can stimulate diclofenac biodegradation in wastewater treatment. Finally, resource recovery is one of the major initiatives in the wastewater treatment field. WWTPs are no longer seen as just treatment facilities, but also present opportunities to recover other added-value products and provide more sustainable solutions. Phosphorus is an irreplaceable nutrient and a scarce resource that must be recovered from phosphorus rich waste streams. Biological acidification was tested in this study as an additional step within conventional WWTPs and was shown to have great potential to solubilise up to 80 % of phosphorus and produce on average 0.35 g CODVFA/gVS that could be used in subsequent processes for the production of phosphorus rich fertilizers or bioplastics, respectively.